Fibroblast Growth Factor 2‐Mediated Regulation of Neuronal Exosome Release Depends on VAMP3/Cellubrevin in Hippocampal Neurons. Issue 6 (28th January 2020) - Kumar, Rohit; Tang, Qilin; Müller, Stephan A.; Gao, Pan; Mahlstedt, Diana; Zampagni, Sofia; Tan, Yi; Klingl, Andreas; Bötzel, Kai; Lichtenthaler, Stefan F.; Höglinger, Günter U.; Koeglsperger, Thomas
Abstract: Extracellular vesicles (EVs) are endogenous membrane‐derived vesicles that shuttle bioactive molecules between glia and neurons, thereby promoting neuronal survival and plasticity in the central nervous system (CNS) and contributing to neurodegenerative conditions. Although EVs hold great potential as CNS theranostic nanocarriers, the specific molecular factors that regulate neuronal EV uptake and release are currently unknown. A combination of patch‐clamp electrophysiology and pH‐sensitive dye imaging is used to examine stimulus‐evoked EV release in individual neurons in real time. Whereas spontaneous electrical activity and the application of a high‐frequency stimulus induce a slow and prolonged fusion of multivesicular bodies (MVBs) with the plasma membrane (PM) in a subset of cells, the neurotrophic factor basic fibroblast growth factor (bFGF) greatly increases the rate of stimulus‐evoked MVB‐PM fusion events and, consequently, the abundance of EVs in the culture medium. Proteomic analysis of neuronal EVs demonstrates bFGF increases the abundance of the v‐SNARE vesicle‐associated membrane protein 3 (VAMP3, cellubrevin) on EVs. Conversely, knocking‐down VAMP3 in cultured neurons attenuates the effect of bFGF on EV release. The results determine the temporal characteristics of MVB‐PM fusion in hippocampal neurons and reveal a new function for bFGF signaling in controlling neuronal EV release. Abstract : Extracellular vesicles (EVs) are endogenous membrane‐derived vesicles that shuttle biomolecules from cell to cell. The molecular mechanisms that modulate EV release in the central nervous system are poorly understood. Here, it is demonstrated that fibroblast growth factor 2 increases the expression of VAMP3/cellubrevin to enhance the release of EVs from hippocampal neurons.